2016
DOI: 10.1038/ni.3458
|View full text |Cite
|
Sign up to set email alerts
|

Germinal center B cells recognize antigen through a specialized immune synapse architecture

Abstract: B cell activation is regulated by B cell antigen receptor (BCR) signaling and antigen internalization in immune synapses. Using large-scale imaging across B cell subsets, we show that in contrast to naive and memory B cells, which gathered antigen towards the synapse center before internalization, germinal center (GC) B cells extracted antigen by a distinct pathway using small peripheral clusters. Both naive and GC B cell synapses required proximal BCR signaling, but GC cells signaled less through the protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
201
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 165 publications
(210 citation statements)
references
References 42 publications
(54 reference statements)
8
201
1
Order By: Relevance
“…These cells upregulate certain genes related to positive selection (such as Myc , Ccnd2 , and Irf4 ), suggesting that these may indeed represent cells undergoing antigen-driven selection (Mueller et al, 2015). However, a recent study in which GC B cells are exposed to antigen displayed on immobilized plasma membrane sheets (PMSs) shows that, differently from antigens in solution, PMS-bound antigen can efficiently activate signaling downstream of the BCR in GC B cells, with the notable exception of nuclear translocation of NF-κB p50, which required CD40 ligation (Nowosad et al, 2016). Thus, while antigen stimulation can under certain circumstances trigger signaling in GC B cells, the key step of NF-κB activation appears to require additional input from T cells.…”
Section: Positive Selection Of High-affinity Clones In the Gcmentioning
confidence: 99%
See 1 more Smart Citation
“…These cells upregulate certain genes related to positive selection (such as Myc , Ccnd2 , and Irf4 ), suggesting that these may indeed represent cells undergoing antigen-driven selection (Mueller et al, 2015). However, a recent study in which GC B cells are exposed to antigen displayed on immobilized plasma membrane sheets (PMSs) shows that, differently from antigens in solution, PMS-bound antigen can efficiently activate signaling downstream of the BCR in GC B cells, with the notable exception of nuclear translocation of NF-κB p50, which required CD40 ligation (Nowosad et al, 2016). Thus, while antigen stimulation can under certain circumstances trigger signaling in GC B cells, the key step of NF-κB activation appears to require additional input from T cells.…”
Section: Positive Selection Of High-affinity Clones In the Gcmentioning
confidence: 99%
“…B cells use the BCR to retrieve antigen deposited on the membranes of other cells (FDCs in the case of the GC) in an affinity-dependent manner (Batista and Neuberger, 2000). By applying tensile force to the antigen-antibody bond, B cells can readily discriminate between ligands with different affinities (Natkanski et al, 2013), and this process appears to be especially efficient in GC B cells due to their distinctive synapse configuration (Nowosad et al, 2016). Antigen retrieved in this fashion can be presented to helper T cells, providing a mechanism whereby T cells can sense B cell affinity indirectly.…”
Section: Positive Selection Of High-affinity Clones In the Gcmentioning
confidence: 99%
“…The lack of mechanical extraction could be caused by the combination of strong biotin-streptavidin tethering and weak forces generated by B cells on PLBs as a result of lateral antigen slippage (Nowosad et al, 2016). To investigate this, we designed a DNA-based tension sensor that is thermodynamically stable but releases the antigen if the B cell applies mechanical forces higher than a low rupture force of ∼12 pN to the BCR-antigen bond (Fig.…”
Section: Mechanical Force Is the Dominant B Cell Antigen Extraction Mmentioning
confidence: 99%
“…Indeed, recent evidence supports an important role for BCR engagement in promoting GC B cell selection and differentiation into PB, despite the inhibition of the BCR signaling pathway in GC B cells (Khalil et al, 2012; Mueller et al, 2015; Nowosad et al, 2016). One study found that blocking GC B cells’ ability to acquire Ag inhibited initial PB differentiation more effectually than blockade of CD40 or depletion of Tfh cells (Kräutler et al, 2017).…”
Section: Introductionmentioning
confidence: 99%